ANALYSIS OF CONSUMER BEHAVIOR IN MAKING DECISIONS TO PURCHASE MPV CARS IN PEKANBARU CITY - Alif Rahman; Awliya Afwa (Jurnal Apresiasi Ekonomi, 2025)
This study aims to analyze consumer behavior in decision-making when purchasing Multi Purpose Vehicles (MPVs) in Pekanbaru City. MPVs dominate Indonesia's automotive market due to their versatile features and comfort, especially for family use. A descriptive research approach was employed, using questionnaires distributed to 134 respondents who had purchased or used MPVs. The study examined demographic factors (age, gender, education, occupation, and income) as well as various dimensions of consumer behavior, including purchase motives, influences on decision-making, sources of information, timing of purchase, payment methods, and post-purchase satisfaction. The results show that the Toyota Avanza is the most dominant brand, chosen by consumers from various age groups and economic backgrounds. Key reasons for purchasing MPVs include spacious capacity, comfort, and advanced features. Family influence plays a major role in purchasing decisions. Most consumers purchase vehicles through authorized dealers and prefer cash or bank-financed payments. This research contributes to a better understanding of MPV consumer preferences and offers strategic insights for automotive producers and marketers. Keywords: consumer behavior, purchase decision, MPV, consumer preference, Pekanbaru.